Lexicographic analysis of phraseological terms - Karshieva Shakhnoza Tohirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides an overview of phraseological terms and analyses by various scholars in the field. Attempts have been made to prove theories through examples of phraseological terms in English.